Financial Management and Implementation of Catur Purusa Artha Teachings in Ayu Rahayu MSMEs: an Ethnographic Study - Rahayu, Ni Made Astini; Willdahlia, Ayu Gede; Sudianti, Ni Made; Maisusanto, Eko (SEAN Institute, 2025)
In Bali, economic growth has encouraged local communities to develop micro, small, and medium enterprises (MSMEs), especially in trade and services related to Hindu religious ceremonies. However, the pursuit of profit-oriented business practices frequently encounters tensions with the preservation of religious and spiritual values. This dynamic highlights a fundamental disjunction between the maximization of economic gain and the philosophical tenets of Hinduism, particularly Catur Purusa Artha. This research aims to understand the meaning of the serati banten profession in the context of Balinese culture through an ethnographic approach, using the conceptual framework of Catur Purusa Artha which includes aspects of Dharma, Artha, Kama, and Moksa. The urgency of this research problem lies in the need to bridge the gap between business practices and the application of religious values in the management of MSMEs, particularly those operating in the field of religious services, such as the Ayu Rahayu MSME.The qualitative ethnographic approach was used to explore the experiences and views of informants in depth, with data collection techniques through participatory observation, in-depth interviews, and documentation. The results showed that the profession of serati banten is not only positioned as an economic activity, but as a form of spiritual devotion based on the value of sincerity in carrying out yadnya. Material gain (Artha) is understood as the result of work based on Dharma, while the fulfillment of life needs (Kama) is more oriented towards family welfare. In addition, an attitude of resignation, tolerance, and not being attached to worldly gains reflects the achievement of Moksa values. These findings indicate that traditional economic activities in Balinese society have a strong religious dimension, and spiritual values remain the foundation of business management. This research contributes to the understanding of culture and spirituality-based economic practices within the Balinese Hindu framework.